Analisis Faktor-Faktor Produksi yang Memengaruhi Hasil Tangkapan Pancing Ulur (Hand Line) yang Didaratkan di PPS Bungus Sumatera Barat - Hariski, M; Lestari, Anggun; Pramusintho, Bagus; Firmansyah, Firmansyah; Harahap, Afriani; Ramadan, Fauzan (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Hand line is the fishing gear that catches the most tuna compared to tuna longline fishing gear. This is because hand line is an effective fishing gear for catching tuna due to its construction which is able to reach the swimming depth of tuna. Increases and decreases in fish catches are very dependent on fishing activities and various supporting factors in fishing activities. increase. The results showed that the composition of the total number of handline catches during the research at Bungus PPS obtained an average overall catch of 27 individuals with an average weight of 1,095 Kg. There is a difference in the composition of fish caught using handlines in Bungus PPS. The factors that influence the production of hand line catches are the size of the ship (Gt), length of trip/going out to sea, number of fishing gear used and length of hand line. The sum of the parameter coefficients of the Douglas Cobb regression equation is 2.226. This value indicates an elasticity value greater than 1 which means the production (catch) of handline fishing gear is in the increasing return to scale category.